Kehidupan Anak Yang Orang Tuanya Poligami di Desa Sagu Flores Timur - Zahidah Azzah Faizah; Muh. Zaim Azhar (LPPM STIS Hidayatullah, 2022)
This study is motivated by the existence of the life of children in polygamous families. At the age of vulnerable children with surrounding conditions, the task of parents in accompanying and helping to meet the needs of children is very important. Polygamous parents certainly know the additional burdens of polygamy in Islam. The purpose of this study is to find out the life of children whose parents are polygamous by reviewing Islamic law. This type of research is a descriptive field study. In data collection, researchers use interview techniques to informants and observations, as well as data analysis with data reduction, data display, and data verification. From this study it was found that children's lives are fulfilled in terms of biophysical. However, 3 out of 4 children in other needs such as mental, social and spiritual terms are not well met. The conclusion of this study, which is reviewed from Islamic law, is only fulfilled in terms of finances. However, there will be no mental, social and spiritual needs that are a priority in Islam. So that this unbalanced thing makes children abandoned in terms of spirituality, and this is not in accordance with Islamic law.